CLIL (CONTENT AND LANGUAGE INTEGRATED LEARNING) FOR ACHIEVING POSITIVE OUTCOMES OF STUDENTS COLLEGE OF ENGLISH PROGRAM - Khulaifiyah Khulaifiyah (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2015)
CLIL  is  a  methodological  approach  particularly  suitable  for  contexts where students  learn content  through supplementary  teaching materials. The goal of the study is know the positive outcome of Students College after and during the CLIL  applied  on  skill  subjects.  The  sample  of  this  research  was  semester  six students of  Islamic University of Riau who were  taking Microteaching and ESP subject. Clustering random sampling was used here. The  design  of  the  research  was  an  experiment  research  focus  on  Post equivalent  research. The  instruments were  questionnaires,  and  observation. The treatment was given for 8 meetings in form of the students assignment in giving motivation (story, Al-Quran verse, wise words) for about 5 to 7 minutes. Based on the result, the data showed that there is significant effect of CLIL on the students outcome of these subjects. The effect of CLIL was the students were stimulated to hear other motivation activities;  the students were familiar with  the moral values which affected  their  life  style, mind set and behavior. The conclusion was CLIL stimulate students Perception, Moral Perception, spiritual Perception and appear Positive Habits.